Dynamics of marine vehicles with aerodynamic surfaces - Collu, Maurizio (Cranfield University, 2008)
An assessment of the relative speeds and payload capacities of airborne and waterborne vehicles highlights a gap which can be usefully filled by a new vehicle concept, utilizing both hydrodynamic and aerodynamic forces. A high speed marine vehicle equipped with aerodynamic surfaces (called an AAMV, 'Aerodynamically Alleviated Marine Vehicle') is one such concept. The development of this type of vehicle requires a mathematical framework to characterize its dynamics taking account of both aerodynamic and hydrodynamic forces. This thesis presents the development of unified and consistent equations of equilibrium and equations of motion to predict the dynamic performance of such AAMV configurations. An overview of the models of dynamics developed for Wing In Ground effect 'WIGe' vehicles and high speed marine vehicles (planing craft) is given first. Starting from these models, a generic AAMV configuration is proposed and a kinematics framework is developed. Then, taking into account the aerodynamic, hydrostatic and hydrodynamic forces acting on the AAMV, equations of equilibrium are derived and solved. This is followed by deriving and solving the full equations of motion, using a small perturbation assumption. A static stability criterion, specific for the AAMV configuration, has been developed. This mathematical framework and its results are implemented in MATLAB and validated against theoretical and experimental data. The resultant capability for analysing novel AAMV configurations is presented through two parametric analysis. The analysis demonstrate that these models offer a powerful AAMV design tool.